LKPD examination and audit mechanism (considering the opinion of the WWTP conducted to assess regional accountability and financial transparency by the BPK) - Muslimin Muslimin; Wendy Aprianto (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
BPK's audit and game theory audit analysis were carried out by conducting an interview approach with several experts in order to develop a modeling game. Game theory analysis is carried out to compile based on utility modeling. Then each utility model will be measured and obtained using the backward induction method. Based on the results of the game modeling, it was found that in the BPK examination, when the government was compliant or disobedient in the negotiation process, it became a very credible process. This is in accordance with the existing audit mechanism because BPK has advantages in terms of audit. The difference between government scrutiny and the bad nature of institutions compared to credible institutions, namely the corrupt nature of the government, will result in a negotiation process that can be carried out easily. The government's initiative to establish communication with BPK is used by extortion to increase BPK's utility. Initiatives for corrupt behavior can be initiated by both parties. This shows the existence of corrupt practices caused by the superiority of the institution and the existence of information gaps carried out by the BPK. These institutional advantages and gaps have given rise to the practice of manipulating findings.